Hubungan Kecepatan Lari 40 M Dengan Hasil Lompat Jauh Gaya Jongkok Siswa Kelas V SDN 019 Sukaramai Kec. Tapung Hulu Kab. Kampar - Sangidah '; Slamet '; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Based on the researcher’s of male student in class V of SDN 019 Rambah while do long jump, research found while student do run start was not optimal. The purpose of this research is to the correlation of 40 meters running speed with long jump result with squat style student in class V of SDN 019 Sukaramai Tapung Hulu District of Kampar Regency. Population in this research were all students in class V of SDN 019 Rambah amount 101 people. Research instrument used simple correlation. Data were analyzed by product moment correlation. Based on research results, it can be concluded as follows : there is contribution 40 meters running speed with the result of long jump with squat style. Which shows rhitung = 0,334 > rtabel = 0,266Key word : 40 yard running speed, long jump.